Globalized Africa: Political, social and economic impact - Ninsin, K.A. (Globalized Africa: Political, Social and Economic Impact, 2012)
Is globalization beneficial to Africa? Does it open infinite opportunities for economic growth, development and social transformation of the continent? It is the assertion of contributions to this collection that for Africa, globalisation is a counter-revolutionary movement that is stalling the drive of the continent's societies to transform themselves into developed and prosperous entities - just as slavery and colonialism. Included are contributions from eminent scholars such as Samir Amin, Horace Campbell, Thandika Mkandawire and Cyril Obi. © Freedom Publications. All rights reserved.